Functional characterization of ether-a-go-go-related gene potassium channels in midbrain dopamine neurons: implications for a role in depolarization block - Ji, Huifang (2012)
Bursting activity by midbrain dopamine neurons reflects the complex interplay between their intrinsic pacemaker activity and synaptic inputs. Although the precise mechanism responsible for the generation and modulation of bursting in vivo has yet to be established, several ion channels have been implicated in the process. Previous studies with nonselective blockers suggested that ether-a-go-go-related gene (ERG) K(+) channels are functionally significant. Here, electrophysiology with selective chemical and peptide ERG channel blockers (E-4031 and rBeKm-1) and computational methods were used to define the contribution made by ERG channels to the firing properties of midbrain dopamine neurons in vivo and in vitro. Selective ERG channel blockade increased the frequency of spontaneous activity as well as the response to depolarizing current pulses without altering spike frequency adaptation. ERG channel block also accelerated entry into depolarization inactivation during bursts elicited by virtual NMDA receptors generated with the dynamic clamp, and significantly prolonged the duration of the sustained depolarization inactivation that followed pharmacologically evoked bursts. In vivo, somatic ERG blockade was associated with an increase in bursting activity attributed to a reduction in doublet firing. Taken together, these results show that dopamine neuron ERG K(+) channels play a prominent role in limiting excitability and in minimizing depolarization inactivation. As the therapeutic actions of antipsychotic drugs are associated with depolarization inactivation of dopamine neurons and blockade of cardiac ERG channels is a prominent side effect of these drugs, ERG channels in the central nervous system may represent a novel target for antipsychotic drug development.